Effect of divalent minerals on the bioaccessibility of pure carotenoids and on physical properties of gastro-intestinal fluids. (15th April 2016) - Corte-Real, Joana; Iddir, Mohammed; Soukoulis, Christos; Richling, Elke; Hoffmann, Lucien; Bohn, Torsten
Highlights: Divalent minerals reduced solubility of carotenoids following simulated digestion. Bioaccessibility reduction was stronger for calcium than zinc or magnesium. Sodium slightly enhanced the bioaccessibility of carotenoids during digestion. Bioaccessibility correlated with digesta viscosity, inversely with surface tension. Observed effects were generally more pronounced for xanthophylls than for carotenes. Abstract: During digestion, high concentrations of divalent minerals (DMs) can lead to insoluble lipid–soap complex formation, hampering carotenoid bioaccessibility. The effect of varying concentrations (0–1000 mg/L) of calcium, magnesium, zinc and sodium (control) on the bioaccessibility of lutein, neoxanthin, lycopene and β-carotene, following in vitro gastro-intestinal digestion (GI), was investigated systematically and coupled with physical measurements of the digesta. Addition of DMs significantly decreased ( p  < 0.001) carotenoid bioaccessibility, up to 100% in the case of calcium. Mean half maximal inhibitory concentrations (EC50) for calcium, magnesium and zinc were 270 ± 18, 253 ± 75 and 420 ± 322 mg/L respectively. Increased DM concentrations correlated with decreased viscosity ( r  > 0.9) and decreased carotenoid bioaccessibility. Surface tension of digesta correlated inversely ( p  < 0.05) with the bioaccessibility of carotenoids. This correlation was mineral and carotenoid dependent. Although based on in vitro findings, it is plausible that similar interactions occur in vivo, with DMs affecting the bioaccessibility and bioavailability of carotenoids and other lipophilic micronutrients and phytochemicals.